Binary adsorption of CO2/CH4 in binderless beads of 13X zeolite - Silva, José A.C. (2015)
The binary sorption CO2 and CH4 in binderless beads of 13X zeolite has been investigated between 313 and 473 K and total pressure up to 5 atm through fixed bed adsorption experiments. The amount adsorbed of CO2 and CH4 is around 4.7 mmol/gads and 0.4 mmol/gads, respectively, at 313 K and 3.7 atm in a 50/50 equimolar mixture. In a 25(CO2)/75(CH4) mixture the amount adsorbed is 4.0 and 0.84 mmol/g at the same temperature and pressure. Experimental selectivities CO2/CH4 range from 37 at a low pressure of 0.667 atm to approximately 5 at the high temperature of 423 K. Comparing these values with the ones in literature CO2 adsorption capacity is 20% higher than in CECA 13X binder pellets. The CO2/CH4 binary isotherms were fitted with the extended Fowler model that takes into account interaction between adsorbed molecules at adjacent sites suggesting a moderate attraction between CO2 and CH4. The model is validated through a graphical method using the single component isotherm parameters. The breakthrough curves measured show a plateau of pure CH4 of approximately 6 min depending of the operating conditions chosen.